EVALUASI LAHAN PEMBANGUNAN IBU KOTA KABUPATEN YALIMO, PROVINSI PAPUA PEGUNUNGAN - Jitmau, Yowel; Rusim, Dewi Ana; Manalu, Janviter (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2023)
Evaluation of Land Spatial Planning for the Development of the Capital City of Yalimo Regency. Yalimo Regency is a new division of Jatawijaya Regency, with the product of Law Number 4 of 2008 dated January 4, 2008, concerning the formation of Yalimo Regency, Papua Province, which consists of five (5) districts namely: The districts of Elelim, Abenaho, Apalapsili, Benawa, and Welarek, with three hundred (300) villages spread across five districts, with a total population of Yalimo district, sixty-three (63). especially the population of the Elilim District, the capital of the Yalimo Regency. Based on the RDTR of Yalimo Regency, which is located in Elilim, the development of this area aims to build a dream city in the future that is green, sustainable, and integrated. A city that has very good prospects because it is very easy to arrange and organize in terms of the area of spatial land that is divided into three zones namely zone one elelim, zone two Hobakma, and zone three kilometers (km ) 120 Based on Law Number 25 of 2004 concerning the national development planning system, regional governments are given the mandate to develop a systematic and unidirectional development plan. The plan is set out in the form of a Regional Medium-Term Development Plan (RPJMD) for five years. The RPJMD document is a document that contains development plans to respond to various problems from various affairs. The document will be used as a guide in carrying out regional development, as well as to translate the vision and mission of regional heads. in addition, the preparation of the RPJMD becomes very crucial because the RPJMD is the guiding basis for the preparation of strategic plans (Renstra) for all regional apparatuses in Yalimo Regency so that they are more effective, efficient, and focused on providing measurable impacts. Regulation of the Regent of Yalimo Regency Number 8.2013, Concerning the Spatial Planning for Yalimo Regency for 2013-2033. That is to direct the development of Yalimo Regency by utilizing regional space in an efficient, effective, harmonious, balanced, and regional manner.